On sufficiency and duality for nonsmooth multiobjective programming problems involving generalized V – r -invex functions - Ahmad, I.; Gupta, S.K.; Jayswal, Anurag (Nonlinear analysis, 2011)
In this paper, a class of nonsmooth multiobjective programming problems with inequality constraints is considered. We introduce the concepts of V – r -pseudo-invex, strictly V – r -pseudo-invex and V – r -quasi-invex functions, in which the involved functions are locally Lipschitz. Based upon these generalized V – r -invex functions, sufficient optimality conditions for a feasible point to be an efficient or a weakly efficient solution are derived. Appropriate duality theorems are proved for a Mond–Weir-type dual program of a nonsmooth multiobjective programming under the aforesaid functions.